FLIP TEACHING“ ALS DER INNOVATIVE WEG DES FREMDSPRACHENLERNENS - .Rakhmatov, Abror. (Журнал иностранных языков и лингвистики, 2021)
The article describes the "Flip Teaching" methodology as a modern innovative technology for learning foreign languages and its differences from other methods.